Implication of Modern Complementary Foods in Critical Period for Child Health Programming - Tatyana V. Turti; Irina A. Belyaeva; Marina A. Snovskaya; Olga L. Lukoyanova; Elena P. Zimina; Elena A. Bakovich; Zulfiya F. Zokirova; Maria D. Mitish; Ekaterina G. Bokuchava; Anastasia G. Selivanovа (Педиатрическая фармакология)
The current development of medicine and the results of recent large-scale academic research in pediatrics provide the convincing conclusions that the formation of human health begins in the antenatal period of ontogenesis and continues throughout the infancy. The ideas and subsequent academic research on the influence of nutrition during the first thousand days of life on the programming of metabolism and the development of some chronic somatic diseases such as obesity, hypertension, coronary heart disease have become widespread. In addition, at the same period of life immune abnormalities with a predominance of one of the subpopulations, Th1 or Th2, can possibly form in children at risk of developing allergies when immune response is developing. The predominance of the Th2 cytokine profile (hyperproduction of interleukins 4, 5, 13, etc.) suggests the possibility of stable formation of the atopic status in a child afterwards. Consequently, the application of academic knowledge on the health status programming by nutrition during early ontogenesis is an important tool in preventive pediatric practice.